2020
DOI: 10.1097/meg.0000000000001523
|View full text |Cite
|
Sign up to set email alerts
|

Only one-third of hepatocellular carcinoma cases are diagnosed via screening or surveillance: a systematic review and meta-analysis

Abstract: Background/objects Early hepatocellular carcinoma diagnosis is associated with better long-term survival. Studies of at-risk patients who are monitored in routine practice have reported an overall adherence rate to hepatocellular carcinoma screening/surveillance of approximately 60% and suboptimal diagnostic efficacy of the current screening/surveillance tools. However, it is unclear how many hepatocellular carcinoma patients were actually diagnosed via screening/surveillance given these obstacles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…Particularly, in patients with CHB, the pooled adherence rate for HCC surveillance was only 32% (95% CI 13%‐51%) which is consistent globally and in both cirrhotic (36%) and non‐cirrhotic (22%) 121 . (Table 3) As a result, only about one‐third of HCC were diagnosed at pre‐symptomatic stage globally, according to meta‐analysed data from 5875 viral hepatitis‐related HCC cases 119 …”
Section: Gaps In Screening and Surveillance For Hccmentioning
confidence: 82%
See 1 more Smart Citation
“…Particularly, in patients with CHB, the pooled adherence rate for HCC surveillance was only 32% (95% CI 13%‐51%) which is consistent globally and in both cirrhotic (36%) and non‐cirrhotic (22%) 121 . (Table 3) As a result, only about one‐third of HCC were diagnosed at pre‐symptomatic stage globally, according to meta‐analysed data from 5875 viral hepatitis‐related HCC cases 119 …”
Section: Gaps In Screening and Surveillance For Hccmentioning
confidence: 82%
“…A previous study from a tertiary centre in Northern California showed that 22.1% of HCC were HBV‐related 116 . Therefore, major guidelines recommend HCC surveillance via ultrasound with or without AFP every 6 months among high‐risk individuals (ie cirrhosis from any etiologies and high‐risk patients with CHB) so that HCC can be identified in its earliest stages to allow for curative therapy and improved survival 28,117‐119 …”
Section: Gaps In Screening and Surveillance For Hccmentioning
confidence: 99%
“…Globally, only 37% of HCC is diagnosed through surveillance, with < 20% of patients undergoing surveillance per recommended guidelines in USA [61,62]. Barriers include patient, clinician, and health system factors (Fig.…”
Section: Barriers To Surveillancementioning
confidence: 99%
“…Most models include a clinical coordinator and, depending on the location of the patient group, may be based at a tertiary centre, in primary care or in other facilities accessible and appropriate for patients . Adherence rates in patients may be improved using memory triggers, linguistic aids and reminder systems for both patients and providers . A cost‐effectiveness clinical trial of such a model is currently underway and will report its outcomes in 2021 (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=372421).…”
Section: How Do We Achieve It?mentioning
confidence: 99%